Nyando climate-smart villages farms of the future visit to climate analogues sites - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
On 24 – 29 November 2014 The CGIAR Research Program on Climate Change, Agriculture and Food security (CCAFS), East Africa in collaboration with partners on the ground took 16 farmers on a climate analogues journey. The journey was diverse and allowed farmers to see different agricultural approaches that will work for their future environment. Photos S.Kilungu (CCAFS).